2020
DOI: 10.1186/s13018-020-01896-z
|View full text |Cite|
|
Sign up to set email alerts
|

The therapeutic effect to eldecalcitol + bisphosphonate is superior to bisphosphonate alone in the treatment of osteoporosis: a meta-analysis

Abstract: Background Osteoporosis is a metabolic bone disease. Bisphosphonate (BP) and eldecalcitol (ELD) are two clinical first-line drugs for osteoporosis patients. However, the effect of ELD + BP vs. BP alone on osteoporosis treatment is still unclear. The present meta-analysis was conducted to evaluate the different therapeutic effect of BP + ELD vs. BP alone in osteoporosis treatment. Methods Eligible documents that selected from online d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…performed a meta-analysis of four studies and found that ED-71 plus bisphosphonate was associated with high FN-BMD and hip BMD after 6 months compared with bisphosphonate alone. Moreover, these effects were not observed after 12 months, while ED-71 plus bisphosphonate was associated with high lumbar spine BMD after 12 months compared with bisphosphonate alone ( 30 ). However, the analysis of this study was based on two RCTs and two observational studies, and the pooled results might be affected by uncontrolled biases.…”
Section: Discussionmentioning
confidence: 99%
“…performed a meta-analysis of four studies and found that ED-71 plus bisphosphonate was associated with high FN-BMD and hip BMD after 6 months compared with bisphosphonate alone. Moreover, these effects were not observed after 12 months, while ED-71 plus bisphosphonate was associated with high lumbar spine BMD after 12 months compared with bisphosphonate alone ( 30 ). However, the analysis of this study was based on two RCTs and two observational studies, and the pooled results might be affected by uncontrolled biases.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is characterized by an age-related loss of skeletal muscle mass and strength, with decline in hormone levels and number of neuromuscular junctions, increased inflammation, and decline in the physical activity or inadequate nutrition ( Santilli et al, 2014 ). Osteoporosis is a progressive bone disease that causes weak and brittle bones, a decrease in bone mass and density leading to debilitating fragility fractures ( Zeng et al, 2019 ; Zheng and Luo, 2020 ). Both these diseases also reduce the quality of life and mobility, resulting in significant morbidity and mortality ( Noguchi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis causes an estimated 8.9 million fractures worldwide annually in 20%–25% of men ( Zheng and Luo, 2020 ; The Lancet Diabetes and Endocrinology, 2021 ). It is estimated that China alone has 13% prevalence of osteoporosis, and the annual number of osteoporosis-associated fractures is predicted to grow by 4.8 million by 2035 ( Zeng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%